A Review: Plant Damage Due to Nutrient Imbalance and Strategies to Increase Nutrient Efficiency - Ma'ruf, Amar; Syahminar, Syahminar (Tropical Plantation Journal, 2024)
The nutritional state of a plant can range from acute poisoning to acute deficiency. For broad purposes, it could be helpful to categorize the nutritional status into four groups: surplus, ideal, inadequate, and extensive. Nutrients that are considered essential include boron (B), iron (Fe), manganese (Mn), copper (Cu), zinc (Zn), nickel (Ni), molybdenum (Mo), calcium (Ca), magnesium (Mg), sulfur (S), and chlorine (Cl). Every nutrient has an effect on the metabolism of plants at every stage of their growth. Of course, breeding techniques are used to improve the efficiency with which plants take nutrients, such as enhancing nutritional utilization and optimizing nutritional efficiency through root modifications. In nutrient-poor soils, for instance, optimizing root shape to boost nutrient uptake efficiency can boost plant output. While developing organs, particularly reproductive organs, transpire at low rates, they need a lot of mineral resources to expand actively. Plants' nutritional efficiency may be effectively increased by using genetic engineering to transfer genes from other species, so overcoming the restrictions imposed by genetic variation within the same species.